Superluminescence from an optically pumped molecular tunneling junction by injection of plasmon induced hot electrons - Braun, Kai; Wang, Xiao; Kern, Andreas M.; Adler, Hilmar; Peisert, Heiko; Chassé, Thomas; Zhang, Dai; Meixner, Alfred J. (Beilstein Journal of Nanotechnology, 2015)
Here, we demonstrate a bias-driven superluminescent point light-source based on an optically pumped molecular junction (gold substrate/self-assembled molecular monolayer/gold tip) of a scanning tunneling microscope, operating at ambient conditions and providing almost three orders of magnitude higher electron-to-photon conversion efficiency than electroluminescence induced by inelastic tunneling without optical pumping. A positive, steadily increasing bias voltage induces a step-like rise of the Stokes shifted optical signal emitted from the junction. This emission is strongly attenuated by reversing the applied bias voltage. At high bias voltage, the emission intensity depends non-linearly on the optical pump power. The enhanced emission can be modelled by rate equations taking into account hole injection from the tip (anode) into the highest occupied orbital of the closest substrate-bound molecule (lower level) and radiative recombination with an electron from above the Fermi level (upper level), hence feeding photons back by stimulated emission resonant with the gap mode. The system reflects many essential features of a superluminescent light emitting diode.
Keywords: inelastic tunneling; light emitting diode; quantum plasmonics; scanning near-field optical microscopy; tip-enhanced Raman spectroscopy